Longitudinal Predictors of Listening Comprehension in Bilingual Primary School‐Aged Children. Issue 1 (17th July 2022) - Valentini, Alessandra; Serratrice, Ludovica
Abstract: Research on monolingual children has shown that listening comprehension is predicted by a range of language and cognitive skills; less is known about predictors of listening comprehension in bilingual children and about the role of language input. This study presents longitudinal data on predictors of English listening comprehension in 100 bilingual children between the ages of 5;8 and 6;8 years. The children were tested three times on their literal and inferential comprehension of stories. Vocabulary, morphosyntax, attention, and memory were included as predictors of listening comprehension alongside a measure of English input. The children showed growth over time in both literal questions and global inference questions, with performance on local inferences remaining stable over time. Vocabulary depth and morphological knowledge explained listening comprehension abilities in all types of questions, but not their growth; that is, all children improved in comprehension over time regardless of their initial morphological and vocabulary depth skills. English input had a mediated effect on listening comprehension via morphological knowledge and vocabulary depth, but no direct effect. Abstract :